Precautionary politics : principle and practice in confronting environmental risk - Whiteside, Kerry H., 1953- (Urban and industrial environments., 2006)
A study of the precautionary principle-its meaning, its rationale, its policy implications, and the controversies provoked by its use in environmental regulation.